(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
The cyprote.rone acetate (CPA) is an antiandrogen drug that is used in the treatment of prostate cancer, which is related to drug-induced liver injury (DILI). The aim of this study the effect of the water extract of one of the local dates on the side effects of using cyproterone acetate on liver tissue in white mice. Forty from albino mice male were divided into 8 equal groups received orally in one ml as follows. Group 1: distilled water passive control, group 2: corn oil positive control, group 3: received with 5 mg/kg body weight CPA , group 4: received, with 20 mg/kg CPA, group 5: received with 5 mg/kg CPA & 60 mg/kg date palm extract, group 6: received, with 5 mg/kg CPA & 120 mg/kg date palm extract, group 7: received , with 20 mg/kg CPA & 60 mg/kg date palm extract, group 8: received with 20 mg/kg CPA & 120 mg/kg date palm extract lasted for 21 days. Showed a histological study of the liver remarkable degeneration of hepatocytes associated with interstitial necrosis and blood vessel congestion. The current study proved that the water extract of dates has a weak effect in the repair of damage in the liver tissue to treatment for the low dose of cyproterone acetate only